2017
DOI: 10.2147/ndt.s134751
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for the management of postictal agitation after electroconvulsive therapy with S-ketamine anesthesia

Abstract: ObjectivesPostictal agitation (PIA) represents one of the most common complications during a modified electroconvulsive therapy (ECT) course. Its clinical management can be challenging especially in cases with poor response to benzodiazepines. Dexmedetomidine, a highly selective alpha-2 adrenoceptor agonist acting predominantly in the locus coeruleus, exerts sedative effects without causing relevant respiratory depression. To the best of our knowledge, this is the first study that aimed to assess the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
9
0
1
Order By: Relevance
“…In 2016, Aksay et al retrospectively analyzed 7 patients who received 178 ECT sessions between 2011 and 2015. Their analysis revealed that the prevalence of post-ictal agitation was lower in dexmedetomidine recipients and it was suggested that adjunctive use of dexmedetomidine to S-ketamine in ECT may be promising for reducing agitation [1]. The results of our study were similar in relation to the reduction of agitation in the dexmedetomidine group.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In 2016, Aksay et al retrospectively analyzed 7 patients who received 178 ECT sessions between 2011 and 2015. Their analysis revealed that the prevalence of post-ictal agitation was lower in dexmedetomidine recipients and it was suggested that adjunctive use of dexmedetomidine to S-ketamine in ECT may be promising for reducing agitation [1]. The results of our study were similar in relation to the reduction of agitation in the dexmedetomidine group.…”
Section: Discussionsupporting
confidence: 77%
“…Patients with manic episode or both manic and hypomanic episodes are considered as bipolar disorder. A complete diagnostic evaluation must first be performed to treat patients with mood disorders and then a treatment plan can be implemented [1]. At present, existing treatments place particular emphasis on drug therapy combined with psychotherapy; however, the use of electroconvulsive therapy (ECT) may be the best and fastest approach in treatment-resistant depression, psychotic patients, those with suicidal thoughts, and pregnant mothers with severe depression or mania [2].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly acts within the locus coeruleus, produces sedative, hypnotic and anxiolytic effects, activates presynaptic membrane a 2 receptors, inhibits the release of norepinephrine, terminates the transmission of pain signals, and inhibits sympathetic activity and the stress response. 8 Some studies have shown that dexmedetomidine also has certain neuroprotective effects. Zhao et al 9 confirmed that dexmedetomidine has protective and hemodynamic effects in HICH patients during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 ECT causes seizures by electrical stimulation at various frequencies, that is run through electrodes placed on the scalp. 5 Although ECT is a very safe treatment and has no absolute contraindication, both the physician and the patient must be aware of a number of side effects, such as cognitive impairment (which rapidly resolves in most cases), the rare occurrence of seizures, short-term complications such as headaches, muscle pain, nausea, vomiting, and fatigue. 6 ECT typically induces transient hypertension (HTN) and immediate tachycardia after stimulation, which may result in severe hyperdynamic responses in patients treated with ECT.7 One of the short-term side effects of ECT is postictal agitation, 5 which causes motor dysfunction, poor response to verbal materials, and disorientation.…”
mentioning
confidence: 99%